2008
DOI: 10.1097/mao.0b013e31818a0906
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Arteriosclerosis and Changes of the Cochlea in Young Adults

Abstract: Degeneration of the cochlea, especially in the basal turn, was already apparent in young adults with generalized arteriosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 19 publications
(18 reference statements)
0
17
0
Order By: Relevance
“…Evidence of microvascular disease affecting the high‐ and low‐frequency regions of the cochlea has been found in multiple temporal bone studies. Nomiya et al performed a temporal bone cadaver study of young adults (23‐36 years old) with generalized arteriosclerosis compared to age matched controls and found degeneration of the cochlea, especially in the basal turn, of the arteriosclerosis group . Moreover, histopathological studies of aging gerbils has shown similar results with atrophy of the stria vascularis in the apical and basal turns, providing evidence for microvascular involvement in age‐related hearing loss .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Evidence of microvascular disease affecting the high‐ and low‐frequency regions of the cochlea has been found in multiple temporal bone studies. Nomiya et al performed a temporal bone cadaver study of young adults (23‐36 years old) with generalized arteriosclerosis compared to age matched controls and found degeneration of the cochlea, especially in the basal turn, of the arteriosclerosis group . Moreover, histopathological studies of aging gerbils has shown similar results with atrophy of the stria vascularis in the apical and basal turns, providing evidence for microvascular involvement in age‐related hearing loss .…”
Section: Discussionmentioning
confidence: 96%
“…Hearing loss has also been associated with other microischemic pathologies such as retinopathy and chronic kidney disease . A histological study of cadaveric temporal bones has shown that strial atrophy is the most prominent finding in the aging cochlea, and this process is more prominent in elderly patients with presbycusis and also in younger patients with generalized arteriosclerosis compared to aged matched controls . Although these studies support the hypothesis that compromised cochlear vascularity is involved in hearing loss, the relationship to stroke risk score has not been studied.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The stria vascularis requires a high level of blood supply to maintain the endocochlear potential levels and that the impaired homeostasis of the cochlear blood supply due to arteriosclerosis results in degeneration of the stria vascularis (22, 23). A human temporal bone study by Nomiya et al showed that patients with arteriosclerosis had a decreased number of cochlear hair cells, as compared with normal controls (24). In our study, the area of the stria vascularis in our human temporal bone samples from SLE patients was small, but did not significantly correlate with the duration of SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Because degeneration of the cochlea has been found to be apparent in young adults with generalized arteriosclerosis (14), to minimize the potential influence of atherosclerosis in the development of vestibular abnormalities, as previously reported, all AS patients seen during the period of recruitment that had experienced cardiovascular disease, including ischemic heart disease (angina or myocardial infarction electrocardiographically confirmed), heart failure, cerebrovascular events (transient ischemic attacks or strokes confirmed by magnetic resonance imaging and/or computerized tomography brain scan) or peripheral arterial disease (confirmed by Doppler and/or arteriography), or renal insufficiency (serum creatinine values in all individuals included in this study had to be less than 1.3 mg/dl, which is considered the upper normal range in our laboratory), were excluded (4).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%